2007
DOI: 10.1097/01.ijg.0000212274.50229.c6
|View full text |Cite
|
Sign up to set email alerts
|

Travoprost 0.004% With and Without Benzalkonium Chloride: A Comparison of Safety and Efficacy

Abstract: Travoprost 0.004% without BAC is equivalent to travoprost 0.004% with BAC in both safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 20 publications
6
81
0
Order By: Relevance
“…19,22,24 In addition, when comparing travoprost with BAK (Travatan ® ; Alcon Laboratories, Inc., Fort Worth, Texas, USA) to travoprost with sofZia ™ (Travatan Z ® ; Alcon Laboratories, Inc., Fort Worth, Texas, USA), the IOP-lowering effi cacy was found to be identical. 25 Thus, it appears that BAK is not required for either safety or effi cacy of travoprost as an ocular hypotensive agent.…”
Section: Discussionmentioning
confidence: 99%
“…19,22,24 In addition, when comparing travoprost with BAK (Travatan ® ; Alcon Laboratories, Inc., Fort Worth, Texas, USA) to travoprost with sofZia ™ (Travatan Z ® ; Alcon Laboratories, Inc., Fort Worth, Texas, USA), the IOP-lowering effi cacy was found to be identical. 25 Thus, it appears that BAK is not required for either safety or effi cacy of travoprost as an ocular hypotensive agent.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] In particular, Hamacher et al 41 in a pharmacodynamics analysis did not find statistically significant differences between BAK-free and BAKcontaining formulations in the incidence of ocular adverse events comparing preservative-free tafluprost with tafluprost containing 0.01% BAK. Also, in the work of Gross et al 42 , travoprost BAK free and travoprost preserved with BAK showed no differences in the safety and Lewis et al 43 have demonstrated no differences in the incidence of side ocular effects, comparing travoprost 0.004% containing 0.015% BAK with travoprost 0.004% BAK free.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis was performed to determine which of the five medicated gels was most suitable for ophthalmic delivery of cysteamine. Benzalkonium chloride is the most widely used preservative in ophthalmic preparations (Lewis, et al 2007;Marple, et al 2004). …”
Section: Resultsmentioning
confidence: 99%